Auto-avaliação de escolas: processo construído coletivamente nas instituições escolares - Brandalise, Mary Ângela Teixeira (2007)
Different perspectives on the evaluation of schools have of late been the object of analysis and debate in Brazil as in so many other countries. The focus in this case is the school and the process of evaluation it undergoes both internally and externally. Taking into account that the internal evaluation of schools, as a collective process, does not yet constitute a standard practice in most schools, and considering in addition that scientific literature on this theme is still scarce, especially in Brazil, the aim of this research is to organize a significant and effective process of institutional self-evaluation in elementary schools. The point which is addressed is how to work out a process of institutional self-evaluation in elementary schools, by means of concepts, procedures and innovative analytical tools, and with the ultimate aim of achieving institutional development.The subjects of the research are teachers, school employees and parents belonging to a public school in the state of Paraná which provides basic education at the levels of what is known in Brazil as Educação Básica and Ensino Fundamental.The first chapter discusses the theoretical foundations of educational evaluation, pointing out the centrality of this issue in our days: the consequences of the presence of the state as an evaluator, as well as the relations involving school, curriculum and evaluation.In order to deepen the understanding of the conceptions of educational evaluation in relation to the social, political and economic contexts, chapter two investigates the evolution of the conceptions of evaluation, the epistemological areas in which the investigations on evaluation are developed, and the importance of coherence in the development of school evaluation.Chapter three develops a reflection on the theoretical and practical assumptions which underly the process of school self-evaluation, as a result of a joint enterprise and chapter four outlines the methodological procedure, which is called pesquisa-ação institucional (institutional research-action) as well as the procedures involving the documental analysis, the research record, the focal group and the questionnaire.In order to obtain the answers to the closed questions in the questionnaire, the data were tabulated and organized in tables and graphs. The answers to the open questions and to the transcribed discussions of the focal groups were based on the software Qualiquantisoft, a program developed for the methodological procedure Discurso do Sujeito Coletivo DSC (Discourse of the Collective Subject), which enabled the construction of a series of discurse syntheses that make up chapter five. Presented and analyzed in the light of the theoretical framework, these pieces of discourse contribute to the apprehension of the meaning which teachers, parents, students and school employees attribute to the educative actions in the process of school evaluation, creating, in this sense, a colective construction of knowledge concerning self-evaluation. Finally, the research confirms that self-evaluation can be carried out collectively in schools when it is developed in a dialectic-critical fashion, by people belonging to the school community. It is believed, on the one hand, that this research will contribute to rendering explicit the complexity involved in the construction of a process of self-evaluation in schools, and on the other, that it will be able point to new ways for constructing a new culture in school evaluation, capable achieving both professional and institutional development: school self-evaluation as a collective process inside the schools themselves